Assessment of palatal rugae pattern for sex and ethnicity identification in an iranian population - Mahnaz Sheikhi; Mohammad Zandi; Maryam Ghazizadeh (Wolters Kluwer Medknow Publications, 2018)
Background: Palatal rugoscopy is a reliable method in the forensic personal identification and racial group specification. the aim of the present study is to use palatal rugae pattern in sex and ethnicity identification applications. Materials and Methods: Four hundred individual dental casts from four different ethnic populations of Iran were randomly selected. The pattern of the palatal rugae (shape, length, and number) investigated and its reliability to classify sex and minor ethnicity for each individual cast was evaluated. (P < 0.05) considered significant. Results: The most common rugae shapes were straight, followed by wavy and curved types. The least frequent shapes were converging and circular types. Palatal rugae patterns were unique to each person. However, they could not differentiate males and females and had low abilities to classify the racial subsets. Conclusion: The palatal rugae pattern was unique to each individual and palatal rugoscopy can be considered as a reliable forensic identification tool where utilizing other methods such as DNA profiling, fingerprint, and dental record comparison is impossible or difficult. In this study, palatal rugoscopy was not a reliable method to classify the sex of an individual and to differentiate between different racial subsets.